How Molecules with Dipole Moments Enhance the Selectivity of Electrodes in Organic Solar Cells – A Combined Experimental and Theoretical Approach. Issue 19 (12th July 2016) - Würfel, Uli; Seßler, Martin; Unmüssig, Moritz; Hofmann, Nils; List, Mathias; Mankel, Eric; Mayer, Thomas; Reiter, Günter; Bubendorff, Jean‐Luc; Simon, Laurent; Kohlstädt, Markus
Abstract : Simple organic molecules with permanent dipole moments – amino acids and heterocycles – have been successfully employed in bulk‐heterojunction organic solar cells as interlayer between photoactive material and electron contact. A large increase of open‐circuit voltage and fill factor can be observed for four different polymers as donor material in the photoactive layer. A combination of current–voltage curves, scanning Kelvin‐probe atomic force microscopy, ultraviolet photoelectron spectroscopy, and electroluminescence measurements as well as numerical simulations are carried out to clarify in detail the underlying mechanisms. All results fully confirm the hypothesis that the main effect is an accumulation of electrons and a depletion of holes in the photoactive layer in the vicinity of the electron contact induced by a decrease of its effective work function. Further, density functional theory calculations and literature reports of the energy levels of the dipole molecules strongly suggest that the charge carriers tunnel through the thin dipole layer which does however not limit the current. This represents a versatile, simple, and cheap method to realize highly selective contacts which may also be beneficial for other types of solar cells and devices where contact selectivity is crucial. Abstract : Simple organic molecules with permanent dipole moments significantly enhance the selectivity of the electron contact in organic solar cells. They modify the work function of Indium Tin Oxide strongly which is investigated by means of scanning Kelvin‐probe force microscopy, photoelectron spectroscopy, and electroluminescence in combination with numerical simulations. No preferential tunneling of electrons is needed to consistently explain all results.